His dream of passion: reflections on the work of Lee Strasberg and his influence on British actor training. Issue 1 (2nd January 2016) - Shirley, David
Abstract: The first of two 'companion' articles examining the work of Lee Strasberg, this discussion begins with an exploration of Lee Strasberg's interpretation and adaptation of Stanislavski's 'Emotion Memory' exercise before proceeding to examine the efficacy of his version of the technique and consider the extent to which some of the persistent criticisms surrounding his approach are tenable. Has his work been misjudged and misrepresented in recent years or are some of the concerns that have arisen justified? The discussion will then move on offer a brief outline of some of Strasberg's other techniques and consider the degree to which his approach may have influenced actor-training environments in British schools and colleges.